2020
DOI: 10.1111/jam.14476
|View full text |Cite
|
Sign up to set email alerts
|

Role of heterotrophic aerobic denitrifying bacteria in nitrate removal from wastewater

Abstract: With the increase in industrial and agricultural activities, a large amount of nitrogenous compounds are released into the environment, leading to nitrate pollution. The perilous effects of nitrate present in the environment pose a major threat to human and animal health. Bioremediation provides a costeffective and environmental friendly method to deal with this problem. The process of aerobic denitrification can reduce nitrate compounds to harmless dinitrogen gas. This review provides a brief view of the exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(86 citation statements)
references
References 173 publications
2
82
0
2
Order By: Relevance
“…Interestingly, there were significant reduction in nitrate concentrations in all treatments observed after the second week of culture. This reduction might relate to the activity of denitrification bacteria that convert nitrate into nitrite and nitrogen gas which likely to occur at low oxygen concentration (Strauch et al, 2018;Rajta et al, 2019). This confirms previous study by Chen et al (2020) reporting that denitrification might be on going in African catfish biofloc system as indicated by the decrease in nitrate concentrations, the increase of alkalinity and the presence of some genera of bacteria that have the activity in denitrification.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, there were significant reduction in nitrate concentrations in all treatments observed after the second week of culture. This reduction might relate to the activity of denitrification bacteria that convert nitrate into nitrite and nitrogen gas which likely to occur at low oxygen concentration (Strauch et al, 2018;Rajta et al, 2019). This confirms previous study by Chen et al (2020) reporting that denitrification might be on going in African catfish biofloc system as indicated by the decrease in nitrate concentrations, the increase of alkalinity and the presence of some genera of bacteria that have the activity in denitrification.…”
Section: Discussionsupporting
confidence: 82%
“…Figure 1 illustrates the response of strain JD-014 to different carbon sources and nitrate concentrations by comparing the nitrogen removal performance. It has been suggested that carbon source is an important factor affecting denitrification process, since different carbon sources would induce variations in electron transfer process and the associated activity of enzymatic reaction within heterotrophic denitrifiers [ 6 , 26 ]. The results showed in Figure 1 A,B indicate that the cell growth and nitrogen removal performance of JD-014 were quite different among the five tested carbon sources.…”
Section: Resultsmentioning
confidence: 99%
“…To eliminate the problem, various treatment methods such as filtration, ion exchange, physical adhesion, and electrodialysis have been implemented for the removal of nitrate contents before the influent of wastewater into aquatic systems [ 2 ]. Nevertheless, there are several limitations for the practical application of the above technologies, owing to the reality that most of these techniques are associated with high expensive operating costs, complicated operation process, high energy consumption, and the generation of secondary pollution [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, despite the presumably low CBOD 5 entering the SAGRs (plant effluent was <3 mg/L CBOD 5 throughout 2017), genera known for heterotrophic denitrification showed a substantial increase with biofilm age (Carneiro FidĂ©lis Silva et al, 2019; Mrkonjic Fuka et al, 2007; Rajta et al, 2020). Pseudomonas increased from 0.6% to 4.3%, and Bacillus increased from 0.03% to 0.13% relative abundance.…”
Section: Resultsmentioning
confidence: 99%